Right ventricular size and function under riociguat in pulmonary arterial hypertension and chronic thromboembolic pulmonary hypertension (the RIVER study) - Alberto M. Marra; Michael Halank; Nicola Benjamin; Eduardo Bossone; Antonio Cittadini; Christina A. Eichstaedt; Benjamin Egenlauf; Satenik Harutyunova; Christine Fischer; Henning Gall; Hossein Ardeschir Ghofrani; Marius M. Hoeper; et al. (2018)
Riociguat is a soluble guanylate cyclase stimulator approved for pulmonary arterial hypertension (PAH) and chronic thromboembolic pulmonary hypertension (CTPEH). The objective of this study was to evaluate right heart size and function assessed by echocardiography during long term treatment with riociguat.Patients who started riociguat treatment (1.0-2.5 mg tid) within the trials phase II, PATENT, PATENTplus, EAS, CHEST and continued treatment for 3-12 months were included in this study. Echocardiography was analysed off-line at baseline, after 3, 6 and 12 months by investigators who were blinded to clinical data. Last and baseline observation carried forward method (LOCF, BOCF) were performed as sensitivity analysis.Seventy-one patients (45% PAH, 55% CTEPH; 53.5% female; 60 ± 13 years, mean pulmonary arterial pressure 46 ± 10 mmHg, mean PVR 700 ± 282dynes·sec·cm-5) were included. After 6 months, RA and RV area, RV thickness tricuspid regurgitation velocity showed a significant reduction. After 12 months, patients receiving riociguat therapy showed a significant reduction in right atrial (- 2.6 ± 4.4 cm2, 95% CI -3.84, - 1.33; p < 0.001, n = 49) and right ventricular (RV) area (- 3.5 ± 5.2 cm2, 95% CI -5.1, - 1.9; p < 0.001; n = 44), RV thickness (- 0.76 ± 2.2 mm, 95% CI -1.55, 0.03; n = 32), and a significant increase in TAPSE (2.95 ± 4.78 mm, 95% CI 1.52, 4.39; n = 45) and RV fractional area change (8.12 ± 8.87 mm, 95% CI 4.61, 11.62; n = 27). Both LOCF and BOCF showed similar results but lower effect sizes.Patients under long-term treatment with riociguat show significantly reduced right heart size and improved RV function in PAH and CTEPH. Further controlled prospective studies are needed to confirm these results.